Spin-Offs as Microfoundations of Dynamic Capabilities in Rapidly Growing SME - Laviolette, Eric (Management international / International Management / Gestiòn Internacional, 2019)
This paper analyzes how spin-offs can contribute to the micro foundations of dynamic capabilities in rapidly growing SMEs. Building on a multi-case study, three functions of spin-offs are analyzed at a supra level: boundary spanning to sense opportunities, flexible organizing to seize them and ambidextrous orchestration to reconfigure them. At an infra level, dynamic managerial foundations include a repertoire of cognitive, managerial and social skills that both the parent company owner-managers and the spin-off entrepreneurs share. However, they leverage those skills differently in terms of scope, speed and depth, thus complementing each other at different stages of the spin-off process.